Heterogeneity Analysis of Cucumber Canopy in the Solar Greenhouse - Ting-ting QIAN; Sheng-lian LU; Chun-jiang ZHAO; Xin-yu GUO; Wei-liang WEN; jian-jun DU (Journal of Integrative Agriculture)
Detailed analysis of canopy structural heterogeneity is an essential step in conducting parameters for a canopy structural model. This paper aims to analyze the structural heterogeneity of a cucumber (Cucumis sativus L.) canopy by means of analyzing leaf distribution in a greenhouse environment with natural sunlight and also to assess the effect of structural canopy heterogeneity on light interception and photosynthesis. Two experiments and four measurements were carried out in autumn 2011 and spring 2012. A static virtual three-dimensional (3D) canopy structure was reconstructed using a 3D digitizing method. The diurnal variation of photosynthesis rate was measured using CIRAS-2 photosynthesis system. The results showed that, leaf azimuth as tested with the Rayleigh-test was homogeneous at vine tip over stage but turned heterogeneous at fruit harvest stage. After eliminating the influence of the environment on the azimuth using the von Mises-Fisher method, the angle between two successive leaves was 144°; at the same time, a rule for the azimuth distribution in the canopy was established, stating that the azimuth distribution in cucumber followed a law which was positive spin and anti-spin. Leaf elevation angle of south-oriented leaves was on average 13.8° higher than that of north-oriented leaves. The horizontal distribution of light interception and photosynthesis differed significantly between differently oriented leaves. East- and west-oriented leaves exhibited the highest photosynthetic rate. In conclusion, detailed analysis of canopy structural heterogeneity in this study indicated that leaf azimuth and elevation angle were heterogeneous in cucumber canopy and they should be explicitly described as they have a great impact both on light distribution and photosynthesis.